2004
DOI: 10.1038/sj.cgt.7700675
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glioma invasion by overexpression of pigment epithelium-derived factor

Abstract: Pigment epithelium-derived factor (PEDF) is a potent inhibitor of angiogenesis and an inducer of neural differentiation. We previously reported the loss of PEDF expression in glioma progression. In this study, we investigated whether PEDF overexpression could suppress glioma growth and invasion. Glioma cell line U251 was stably transfected with a full-length human PEDF expression vector. The expression and release of various cytokines and angiogenic factors into the medium were analyzed by realtime reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 21 publications
6
64
2
Order By: Relevance
“…Unlike our findings in the PEDF-null mice, previous reports 34,35 had indicated that PEDF and TSP-1 are coordinately regulated. To investigate a potential suppressive effect of PEDF on TSP-1, PEDF was overexpressed in Panc-1 cells (a pancreatic cancer cell line with relatively low PEDF levels).…”
Section: Pedf Levels Modulate the Expression Of The Fibrogenic Regulacontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike our findings in the PEDF-null mice, previous reports 34,35 had indicated that PEDF and TSP-1 are coordinately regulated. To investigate a potential suppressive effect of PEDF on TSP-1, PEDF was overexpressed in Panc-1 cells (a pancreatic cancer cell line with relatively low PEDF levels).…”
Section: Pedf Levels Modulate the Expression Of The Fibrogenic Regulacontrasting
confidence: 99%
“…35 PEDF overexpression in tumor cells similarly increased TSP-1 expression, with transcription factors implicated in this coordinated regulation. 34,37 However, the results from this study suggest that their respective roles in mediating tissue repair are unique. This is suggested by protein structure interactions with the tissue matrix and the phenotype of transgenic mice.…”
Section: Discussionmentioning
confidence: 73%
“…The complete inhibition of metastases with PEDF overexpression strongly indicates that it plays a key antimetastatic role, possibly through regulation of the microenvironment or direct changes in tumor cell phenotype. In a study by Guan et al, 37 decreased cellular invasion of malignant U251 cells was also seen in cells overexpressing PEDF. They showed that this was associated with a significant downregulation in matrix metalloproteinase-9 (MMP-9) activity, which plays an important role in extracellular matrix degradation.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, PEDF may serve as a multifunctional antitumor agent in neuroblastomas, inhibiting angiogenesis while promoting the numbers of Schwann cells and differentiated tumor cells that in turn produce PEDF (172). The loss of PEDF expression was also detected in glioma progression (173). In PEDF-deficient mice, stromal vessels were increased and associated with epithelial cell hyperplasia (174).…”
Section: Non-matrix-derived Inhibitors Of Angiogenesismentioning
confidence: 85%